To complete the square for the quadratic equation \( y = x^2 - 16x + 14 \), follow these steps:
-
Start with the equation: \[ y = x^2 - 16x + 14 \]
-
Rearrange the equation to focus on the \( x \) terms: \[ y = (x^2 - 16x) + 14 \]
-
To complete the square, take the coefficient of \( x \) (which is -16), divide it by 2 to get -8, and then square it to get 64.
-
Add and subtract 64 inside the parentheses: \[ y = (x^2 - 16x + 64 - 64) + 14 \]
-
This can be rewritten as: \[ y = (x - 8)^2 - 64 + 14 \]
-
Simplify: \[ y = (x - 8)^2 - 50 \]
Now we have the equation in vertex form \( y = (x - 8)^2 - 50 \), where the vertex is at \( (h, k) = (8, -50) \).
Thus, the vertex of the function is: \[ \boxed{(8, -50)} \]